Mean resistive index as a prognostic tool for hydronephrosis in patients with acute renal colic: a study in a tertiary care - Ravindernath, M. L.; Reddy, G. Mahender (International Journal of Advances in Medicine, 2017)
Background: Uretolithiasis is one of the most common cause of urinary tract obstruction which leads to the admission into the emergency ward. The detection of urolithiasis or acute renal colic is by the radiography, conventional ultrasonography (US) and intravenous urography (IVU). A colour Doppler USG measures this change as a resistive index (RI) of the arcuate arteries at the corticomedullary junction or the interlobar arteries. Methods: 84 patients between the ages 15-50 years, who were admitted to the Emergency department of our hospital with unilateral renal colic were included into our study. Detailed demographic data was collected from all the patients and they were all subjected to a thorough physical and clinical examination. Bladder ultrasound was taken along with color Doppler for all the patients at the time of admission for every 6 hours. Thus, an increased RI index signifies an obstruction without a dilatation. Results: Left flank pain was slightly more than the right flank pain, although this was not found to be significant. Most of the patients were presented with vomiting or nausea and dysuria was seen in 48 patients. there were 41 cases of hydronephrosis in total and all of them were positive for mean RI. The specificity with the mean resistive index with color Doppler was 90%, while the sensitivity was 100%. Around 95% of the prediction was accurate with mean resistive index, with more than 90% efficiency. Conclusions: The mean resistive index is a very good tool for the diagnosis of hydronephrosis, with a very high level of specificity and sensitivity.